'Awakening the echoes of the ancient faith': the National Pilgrimages to Iona. Issue 2 (November 2021) - Grenier, Katherine Haldane
Abstract : This article examines two pilgrimages to Iona held by the Scottish Roman Catholic Church in 1888 and 1897, the first pilgrimages held in Scotland since the Reformation. It argues that these religious journeys disrupted the calendar of historic commemorations of Victorian Scotland, many of which emphasized the centrality of Presbyterianism to Scottish nationality. By holding pilgrimages to "the mother-church of religion in Scotland" and celebrating mass in the ruins of the Cathedral there, Scottish Catholics challenged the prevailing narrative of Scottish religious history, and asserted their right to control the theological understanding of the island and its role in a "national" religious history. At the same time, Catholics' veneration of St. Columba, a figure widely admired by Protestant Scots, served as a means of highlighting their own Scottishness. Nonetheless, some Protestant Scots responded to the overt Catholicity of the pilgrimages by questioning the genuineness of "pilgrimages" which so closely resembled tourist excursions, and by scheduling their own, explicitly Protestant, journeys to Iona.